KEMAMPUAN MEMBACA PEMAHAMAN MAHASISWA - ST. Y. Slamet (PAEDAGOGIA, 2009)
This research aims to determine a relationship between structure and derivation mastery and reading comprehension ability, either separately or simultaneously. This research was conducted in Surakarta. The population was the students of Elementary School Teacher Education, Teacher Training and Education Faculty (FKIP) UNS, and the samples were 60 students taken by random technique. The instrument for collecting data was achievement tests, whereas the technique analysis for analyzing the data was the statistical technique of regression and correlation. The result of analysis shows that there is positive correlation between structure and derivation mastery and readingcomprehensionsability,eitherseparatelyorsimultaneously.